USING DATABASE MANAGEMENT SYSTEM TO DEVELOP AND IMPLEMENT AN AUTOMATED MOTOR VEHICLE MANAGEMENT SYSTEM - Akomolafe, Dipo Theophilus; Timothy, Naomi; Ofere, Francis (European Scientific Journal, ESJ, 2014)
The automated motor vehicle management system is a system developed for managing the movement of vehicles in and out of an organization. Presently, movemnts of vehicles in most organisations are handled manually bythe security officials that are stationed at the gates. This system is associated with mismanaged data, inaccurate data or no data at all in some instances. Consequently, it is imperative to develop a computerized system to manage data taken from the large number of vehicles that move in and out of organisations in order to deal with cases of theft, proper monitoring of people and vehicles and to provide reliable information for decision making. The proposed system is a window based desktop application designed with Microsoft Access as the database management system under a visual studio environment, Microsoft Visual Basic 6.0. It was tested with data collected over a period of two months and it was able to improve the efficiency, security and professional look of the organization.